Keinginan Pindah Kerja (Turnover Intention) pada Tenaga Kesehatan di Rumah Sakit Umum SM Banyumas Propinsi Jawa Tengah - Panji Anggara; Chriswardani Suryawati; Farid Agushybana (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
Based on the data in SM Banyumas Hospital in 2018, it was identified that in 2016, 2017 and 2018 there were employee turnover as much as 25,9%, 22% and 13%. Eventhough it showed the decreasing rate in each year, but the turnover rate still considered high and could impact negatively for the hospital. This research aimed to analyze factors which cause turnover intention among health workers in SM Banyumas Hospital in Central Java. This was descriptive qualitative research with cross sectional approach. Researh subjects were health workers who already resigned from the hospital and health workers who still actively working in the hospital. Result of the research showed that leadership style, compensation, working partner, and career development are the organizational factors which affect turnover intention among health workers in SM Banyumas Hospital. While there were also external factors which also affect turnover intention. Most respondents stated that there were more interseting and beneficial job offer which caused them to turnover from the SM Banyumas Hospital.